Effects of operation parameters of material handling machines to the applicability - Telek, Péter (Advanced Logistic Systems - Theory and Practice, 2024)
In the past period, the structure and technical elements of material handling machines have changed significantly due to changes in service expectations, technical possibilities and environmental conditions. There are devices that are easier to adapt to certain technical changes, while others may be completely out of industrial use. The purpose of this article is to provide an overview of the most important properties affecting the operation of material handling equipment and to present the relationships between these properties and the applicability. By exploring the relationships between these properties and the most typical areas of application, it is possible to select the most suitable tools. An example task is also presented in the article to show how the method works.